Dermoscopy of melanoma - Tiodorović-Živković, Danica (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Early detection of malignant melanoma is one of the greatest challenges for dermatologists. Dermoscopy is an in vivo method for the early diagnosis of malignant melanoma and the differential diagnosis of pigmented lesions of the skin. We report a 85-year-old man with a pigmented skin lesion in left mandibular region. Dermoscopy revealed evident characteristics of malignant melanoma. The total score was 7 points according to the 7point checklist. Pathohistological examination confirmed diagnosis of melanoma.
Keywords: Aged; Diagnosis; Kožne novotvorbe; Melanom; Melanoma; Microscopy; Mikroskopija; Skin Neoplasms; Starostniki